1992
DOI: 10.1021/bi00142a019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of kinetic constants for the interaction between a monoclonal antibody and peptides using surface plasmon resonance

Abstract: Differences in the affinity of a monoclonal antibody raised against the protein of tobacco mosaic virus for 15 related peptides (residues 134-146) carrying single-residue modifications were investigated using a novel biosensor technology (Pharmacia BIAcore). Analysis of the peptide-antibody interaction in real time allowed fast and reproducible measurements of both association and dissociation rate constants. Out of 15 mutant peptides analyzed, five were not recognized by the antibody at all, and seven were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
90
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(91 citation statements)
references
References 19 publications
1
90
0
Order By: Relevance
“…A previously characterized monoclonal antibody raised against tobacco mosaic virus protein was strongly suspected of binding to an epitope displayed on a contiguous face of an ␣-helix (24). In this particular case, further characterization by alanine scanning and SPR of the antigenic variant peptide corresponding to the original antigen epitope suggested that alanine substitution of a particular glutamic acid, presumably involved in a salt bridge with a vicinal arginine, may affect peptide recognition by stabilizing a conformation that is advantageous to antibody binding (3,24).…”
Section: Discussionmentioning
confidence: 99%
“…A previously characterized monoclonal antibody raised against tobacco mosaic virus protein was strongly suspected of binding to an epitope displayed on a contiguous face of an ␣-helix (24). In this particular case, further characterization by alanine scanning and SPR of the antigenic variant peptide corresponding to the original antigen epitope suggested that alanine substitution of a particular glutamic acid, presumably involved in a salt bridge with a vicinal arginine, may affect peptide recognition by stabilizing a conformation that is advantageous to antibody binding (3,24).…”
Section: Discussionmentioning
confidence: 99%
“…SPR biosensors allow fast and reliable screening of antigens and provide kinetic data on antigen-antibody interactions (Altschuh et al, 1992;Garland, 1996;Schuck, 1997). However, artifacts such as ligand site heterogeneity, ligand steric hindrance, mass-transport limitations, conformational change and non-specific binding have been identified and caution must be taken when considering the kinetic constants as absolute values (Schuck and Minton, 1996;O'Shannessy and Winzor, 1996;Hall et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In typical stopped-flow binding measurements, the protein and ligand are rapidly mixed, and the extent of the reaction is monitored as a function of time using techniques including spectroscopic absorbance (21), fluorescence (10,26,27), enzymatic activity (1,28,29), and surface plasmon resonance (30,31). These techniques are limited by the requirement that the lifetimes of the free and bound states must be severalfold longer than the time required to completely mix the protein and ligand solutions; otherwise, the reaction proceeds nearly to completion before the start of the measurement period.…”
mentioning
confidence: 99%